Factors Affecting Student’s Attitude towards Mobile Advertising: Adnan Farooq (PJDOL, 2023)
The study has been conducted to analyze of the students attitude towards mobile phones. 300 students from different universities and colleges of Islamabad / Rawalpindi were taken. They were of various age groups, academic level, gender and the variables measured are; information, entertainment, irritation and credibility. There were 70% males and 30% female students. According to age there were 29% in the range of 16-20 years; 46% were in the range 21-25; 17% were in the range 25-30 and 9% beyond 30. According to education about 11% are Intermediate, 51% Graduation, 36% Masters and 1 % students are of MS/M-Phil level. The data compiled on the basis of questionnaire shows that almost 53 %students enjoy the SMS and take it as entertainment, 51% receive only specific information as and when required basis. 39% feel irritation by receiving any SMS on their mobiles phones, whereas, 40% even don’t bother to read the full text message, received on their mobiles. Overall 59.7% like mobile advertising.